PROFESSIONAL ACCOUNTANTS LIBRARY. (The Accounting Review, 1954)
The article focuses on a professional accountants library. The graduate class in accounting systems included in its accounting exhibit for the dedication of the new buildings on May 25, 1953, a Professional Accountants Library of approximately 140 books and pamphlets, all recent editions, in accounting and related fields. This Library was on display at the annual convention of the American Accounting Association last September. The books were selected by Alton G. Sadler, Associate Professor, University of North Carolina, and were arranged for publication by Kenneth F. Easter, an M.B.A. Service Scholar. A list of books their author and publishing company have been given. Some of the books included are Principles of Industrial Management by L.P. Alford and H. Russel Beatty published by Ronald Press Co. in 1951. The Impact of Budgets on People by Chris Argyris and Frank B. Miller. Successful Tax Practice by Hugh C. Bickford and published by Prentice Hall. Professional Ethics of Public Accounting by John L. Carey and published by American Institute of Accountants.